Hormesis de herbicidas em soja - Silva, Ferdinando Marcos Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The beneficial effect of low doses of toxic substances is known a long time and this phenomenon is called hormesis. In agriculture, there are many cases of herbicides that in normal rates cause severe injuries in plants, but in very low doses promote the growth of plant structures or other beneficial effect such as increase in the protein content in plants. The objective of this study was to evaluate the effect of hormesis of glyphosate, amicarbazone, mesotrione, imazapic and carfentrazone in soybean, in addition to exploring if the effect of hormesis in soybeans is affected by a pretreatment with low doses of glyphosate and later expose to the same doses or higher. For this, three separate experiments were carried out, and on the first one seven doses of glyphosate (0; 1.8; 3.6; 7.2; 36; 180 and 720 g a.e.ha-1 ) were applied to the soybean plants and evaluated the electron transport rate (ETR), the chemical compounds resulting from the action of glyphosate (shikimic acid, benzoic acid, salicylic acid, AMPA , phenylalanine, tyrosine and tryptophan) and hormesis effect on the dry weight of plants. The second experiment was made a pretreatment of soybean plants with low doses of glyphosate (0; 1.8; 3.6 and 7.2 g a.e.ha-1) in the V2 stage and 14 days later the plants received a second application of different doses of glyphosate (0; 1.8; 3.6; 7.2; 36; 180 e 720 g a.e.ha-1 ) and subsequently evaluated the dry weight of plants and shikimic acid. In the third experiment, was tested a full dose-response of the herbicides amicarbazone, mesotrione, imazapic and carfentrazone on soybean plants and evaluated the ETR and dry weight. The results indicated that at low doses glyphosate stimulated ETR and increased biomass. The compounds from shikimic acid pathway such as benzoic and salicylic acids had respective increases of 203 and 170% in the dose of 3.6 g a.e. ha-1of glyphosate and the amino ...

O efeito benéfico de subdoses de substâncias tóxicas é conhecido há muito tempo e este fenômeno é chamado de hormesis. Em agricultura, muitos são os casos de herbicidas que em doses normais causam severas injurias nas plantas, mas que em doses muito baixas promovem o crescimento de estruturas das plantas ou promovem outros efeitos benéficos, como aumento do teor de proteína em plantas. Objetivou-se com este trabalho avaliar o efeito de hormesis dos herbicidas glyphosate, amicarbazone, mesotrione, imazapic e carfentrazone em soja, além de explorar se o efeito de hormesis na soja é afetado por um pré-tratamento com baixas doses de glyphosate e mais tarde exposta as mesmas doses ou doses maiores. Para isso, três experimentos distintos foram conduzidos, sendo que no primeiro, sete doses do herbicida glyphosate (0; 1,8; 3,6; 7,2; 36; 180 e 720 g e.a.ha-1 ) foram aplicadas sobre as plantas de soja e avaliadas quanto à taxa de transporte de elétrons (ETR), acúmulo de compostos químicos alterados em função da ação do glyphosate (ácido chiquímico, ácido benzoico, ácido salicílico, AMPA, fenilalanina, tirosina e triptofano) e massa de matéria seca das plantas. No segundo experimento, foi feito um pré-tratamento das plantas com subdoses do glyphosate (0; 1,8; 3,6 e 7,2 g e.a. ha-1 ) no estádio V2 e 14 dias após esta aplicação, as plantas receberam uma segunda aplicação de diferentes doses do glyphosate (0; 1,8; 3,6; 7,2; 36; 180 e 720 g e.a. ha-1 ) e posteriormente avaliadas quanto ao acúmulo de massa de matéria seca e ácido chiquímico. No terceiro experimento, foram testadas uma completa curva de dose-resposta dos herbicidas amicarbazone, ...
Keywords: Soja; Plantas – Efeito dos herbicidas; Resistência a herbicidas; Plants, Effect of herbicides on